Pemberdayaan Kelompok Tani Desa Jatimalang, Kabupaten Pacitan melalui Pelatihan Pembuatan Pupuk Organik - Heri Wijayanto; Didik Riyanto; Bambang Triyono; Hakas Putri Wikan Estu (Institut Pertanian Bogor, 2019)
The farmer group of Lestari II, Jatimalang Village, Arjosari Subdistrict, Pacitan Regency has potential in the production of organic fertilizer because it is supported by agricultural residues (straw, corn stalks, soybean stalks, etc.), and livestock waste (animal waste) overflow. Utilization of agricultural and livestock waste is still not optimal. Processing of agricultural and livestock waste into compost carried out by most farmers in Jatimalang Village has not used the fermentation process, so the results and quality are not optimal. The purpose of this farmer group empowerment activity is to provide knowledge about the process of making organic fertilizers from providing raw materials, making bio-activators, and packaging the results of products. The method used is structured training and direct practice of making organic fertilizer. The results obtained from this empowerment activity are that farmer groups are able to make organic fertilizers independently with good quality products, but the stirring process is still not evenly distributed so the granules of organic fertilizer are not the same size.